Predictive molecular pathology in non–small cell lung cancer in France: The past, the present and the perspectives. Issue 9 (4th September 2020) - Hofman, Paul; Rouleau, Etienne; Sabourin, Jean‐Christophe; Denis, Marc; Deleuze, Jean‐François; Barlesi, Fabrice; Laurent‐Puig, Pierre
Abstract : The advent of molecular targets for novel therapeutics in oncology, notably for non–small cell lung carcinoma (NSCLC), led the French National Cancer Institute (INCa) to establish a national network of 28 hospital Molecular Genetics Centers for Cancer (MGCC) in 2007. In each University in France, laboratories were established to develop molecular biology testing to evaluate a few genomic alterations, initially a selection of genes, by using specific targeted polymerase chain reaction (PCR) assays. In a second phase, the number of studied genes was increased. In 2015, the MGCC benefited from an additional dedicated budget from the INCa to develop next‐generation sequencing (NGS) technology. In the meantime, a new financial regulation for innovative testing has been established for the acts out of nomenclature. Consequently, all private and public laboratories in France have access to funding for molecular biology testing in oncology. The gene‐based PCR assays or NGS tests have benefitted from reimbursement of cost testing by the INCa. Today, the laboratories consider this reimbursement to be only partial, and its use to be complex. In 2018, a strategic plan for medical genomic analyses (France Médecine Génomique 2025) was implemented to introduce more systematic sequencing into the health care pathway and oncology practice. The large panel of molecular tests should be centralized to a limited number of molecular genetic centers. This review describes the evolution of the different stages of implementation of molecular pathology testing for NSCLC patients over the last few years in France. Abstract : This review describes the evolution of the different stages of implementation of molecular pathology testing for lung cancer patients in France since 2007. The increasing number of genomic alterations in these patients should be assessed to propose the best therapeutic strategy.